The Role Of Malesi In The Customary Structure Of Amahai Country (Study About Social And Cultural Functions) - Manuputty, Anike JM; Nahuway, Lodewyk; Tanamal, Johan (Arus Jurnal Sosial dan Humaniora, 2025)
Study This aim For study role Malesi in structure customs the people of Negeri Amahai , in particular in context function social and cultural aspects . Malesi is part important in system kinship and government customs , which have task accompany and, if required , replace Lieutenant in various activity customs , including dance war ( Cakalele ). Research This use approach qualitative with technique data collection through observation and interviews deep to figures customs , such as the King of the Country, Saniri of the Country, Kapitan Soa, and Malesi from each question .Research result show that role Malesi No only nature symbolic , but also strategic in guard harmony social , preserving values culture , as well as bridge communication between about and between inhabitant custom . Function social Malesi seen in his contribution to deliberation customs , settlement conflict and coaching generation young . Meanwhile that , function cultural reflected in preservation tradition , delivery message symbolic , and reinforcement identity collective society . In the midst of current modernization , role Malesi experience challenges , but still relevant and necessary preserved through revitalization education custom and wise adaptation.